Human Capital Development, Poverty and Income Inequality in Nigeria (1985-2020) - Ali, Hamisu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Test and Error Correction Model were the tools that were used to estimate the relationship between the variables. Data is from the World Bank Development Indicators (WDI) online database, 2021, Official Gazettes of the Federal Republic of Nigeria, Federal Ministry of Education and Macrotrend, 2021. Empirical results showed that the ratio of human capital to government spending was positive at 5 per cent in the short term, in line with a previous expectation. The long-term relationship between human capital development, poverty and income inequality in Nigeria has been negative. The ECM has a weak rate of adjustment of 1.2 per cent and a 1 per cent significance of this imbalance is corrected annually. Therefore, among other things, it was recommended that the federal government should increase budget allocations for the education and health sectors, and improves living standards through empowerment and the acquisition of self-employment skills.